Jeffrey Nanofluid Flow through a Porous Media Past an Inclined Plate with Effects of Soret Chemical Reaction, and Thermal Radiation - Raju, A. B. Madhumohana; Ananda, K.; Raghunath, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper investigates the heat and mass transfer of an unsteady, MHD incompressible water-based nanofluids (Cu and TiO2) flow over a stretching sheet in a transverse magnetic field with thermal radiation Soret effects in the presence of Heat source and chemical reaction. The governing differential equations are transformed into a set of non-linear ordinary differential equations and solved using a regular perturbation technique with appropriate boundary conditions for various physical parameters. The effects of different physical parameters on the dimensionless velocity, temperature, and concentration profiles are depicted graphically and analyzed in detail. Finally, numerical values of the physical quantities, such as the local skin-friction coefficient, the Nusselt number and the Sherwood number, are presented in tabular form. It is concluded that the resultant velocity reduces with increasing Jeffrey parameter and magnetic field parameter, Results describe that the velocity and temperature diminish with enhancing the thermal radiation. Both velocity and concentration are enhanced with increases of soret parameter. Also it is noticed that the solutal boundary layer thickness decreases with an increase in chemical reaction parameter. It is because chemical molecular diffusivity reduces for higher values of Chemical reaction parameter. Also, water-based TiO2 nanofluids possess higher velocity than water-based Cu nanofluids. Comparisons with previously published work performed and the results are found to be in the excellent agreement. This fluid flow model has several industrial applications in the field of chemical, polymer, medical sciences, etc.